Comparison and Simulation of Riba-free Investment with Riba-based Investment on Real Sector Productivity in Indonesia - Sebastiana Viphindrartin; Eny Lestari Widarni; Aulia Pamasa Setiyantono (Asia Pacific Journal of Management and Education (APJME), 2022)
This study tries to simulate economic growth by using the interest rate as the calculated variable and without the interest rate as the calculated variable. In this study, two calculations were carried out where the first calculation was carried out by regression of Gross Domestic Real Gross as the dependent variable. Investment, consumption, and interest rates as independent variables. The second calculation is the same as the first calculation but omitted the interest rate. From the results of comparing the forecasting results from the threshold autoregressive, indicated that the interest that is used as the cost of capital has an impact on the instability of the real sector.